International Atomic Energy Agency study with referring physicians on patient radiation exposure and its tracking: a prospective survey using a web-based questionnaire. Issue 5 (20th September 2012) - Rehani, Madan M; Berris, Theocharis
Abstract : Objectives: To assess the following themes among referring physicians: (A) importance of acquiring information about previous diagnostic exposures; (B) knowledge about radiation doses involved, familiarity with radiation units and, age-related radiosensitivity; (C) opinion on whether patients should be provided information about radiation dose and (D) self-assessment of appropriateness of referrals. Design: A prospective survey using a web-based questionnaire. Setting: International survey among referring physicians. Participants: Referring physicians from 28 countries. Main outcome measures: Knowledge, opinion and practice of the four themes of the survey. Results: All 728 responses from 28 countries (52.3% from developed and 47.7% from developing countries) indicated that while the vast majority (71.7%) of physicians feel that being aware of history of CT scans would always or mostly lead them to a better decision on referring patients for CT scans, only 43.4% often enquire about it. The majority of referring physicians (60.5%) stated that having a system that provides quick information about patient exposure history would be useful. The knowledge about radiation doses involved is poor, as only one-third (34.7%) of respondents chose the correct option of the number of chest x-rays with equivalence of a CT scan. In total, 70.9% of physicians stated that they do not feel uncomfortable when patients ask about radiation risk from CT scans they prescribe. Most physicians (85.6%) assessed that they have rarely prescribed CT scans of no clinical use in patient management. Conclusions: This first ever multinational survey among referring physicians from 28 countries indicates support for a system that provides radiation exposure history of the patient, demonstrates poor knowledge about radiation doses, supports radiation risk communication with patients and mandatory provisions for justification of a CT examination.